Sprawdź i popraw błędy
a)(2x+y)(x-2y)-x(x+y)=2x do kwadratu-4xy+xy-2ydo kwadratu - x do kwadratu+xy=x do kwadratu-2xy-2ydo kwadratu
b)(3a-2b)(a-b)+2(a-b)(a-2b)=3ado kwadratu-3ab-2ab+2b do kwadratu+2(a do kwadratu-2ab-ab+2b do kwadratu)=5ado kwadratu-10ab+6bdokwadratu
c)(4k+1)(2k-1)-(k-1)(k-3)=8k do kwadratu-4k+2k-1-(kdo kwadratu+3k-k+3)=7kdo kwadratu-4k-4

1

Odpowiedzi

Najlepsza Odpowiedź!
2009-12-03T18:19:15+01:00
A)(2x+y)*(x-2y)-x(x+y)=2x²-4xy+xy-2y²-x²-xy=x²-2y²-4xy
b)(3a-2b)*(a-b)+2(a-b)*(a-2b)=3a²-3ab-2ab+2b²+2(a²-2ab-ab+2b²)=3a²-5ab+2b²+2a²-4ab-2ab+4b²=5a²+6b²-11ab
c)(4k+1)-(k-1)*(k-3)=8k²-4k+2k-1-(k²-3k-k+3)=8k²-2k-1-k²+3k+k-3=7k²+2k-4
5 4 5